7(x-3)=8(x+1)

Simple and best practice solution for 7(x-3)=8(x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(x-3)=8(x+1) equation:


Simplifying
7(x + -3) = 8(x + 1)

Reorder the terms:
7(-3 + x) = 8(x + 1)
(-3 * 7 + x * 7) = 8(x + 1)
(-21 + 7x) = 8(x + 1)

Reorder the terms:
-21 + 7x = 8(1 + x)
-21 + 7x = (1 * 8 + x * 8)
-21 + 7x = (8 + 8x)

Solving
-21 + 7x = 8 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
-21 + 7x + -8x = 8 + 8x + -8x

Combine like terms: 7x + -8x = -1x
-21 + -1x = 8 + 8x + -8x

Combine like terms: 8x + -8x = 0
-21 + -1x = 8 + 0
-21 + -1x = 8

Add '21' to each side of the equation.
-21 + 21 + -1x = 8 + 21

Combine like terms: -21 + 21 = 0
0 + -1x = 8 + 21
-1x = 8 + 21

Combine like terms: 8 + 21 = 29
-1x = 29

Divide each side by '-1'.
x = -29

Simplifying
x = -29

See similar equations:

| -5(-1-2k)=85 | | -15x-20=-12x+100 | | 5(x-2)=6(x+1) | | 4(x-5)=5(x+2) | | 5(12-3w)+25w=2w | | c^2+6c+5=0 | | 272=-8(-4+6a) | | -15x-20=-2x+100 | | 252=-4(7x-7) | | 3(x-2)=4(x+1) | | 18-5x=12+x | | 5(12-3w)+25=2w | | 4r=48 | | 243=27r | | 3x-9=4x | | 5(12-3)+25=2w | | 5x-8=7x | | -2+6n=-80 | | 4x=2x+19 | | ag-14=2g | | 5(x+2)+8=28 | | 49x^2=28x-4 | | 6x^2-15x+14x-35=0 | | 2(x+5)+7=19 | | 5x+4=3x+2 | | -2+6n=-8 | | 3(x+4)+8=2 | | 4x^2=81 | | 55=5(2x+3) | | x^2+8x=-16 | | 12(3x-2)=3(12x+4) | | 42=3(4x+2) |

Equations solver categories